ROLE OF ULTRASOUND IN THE SELECTION OF ACCESS FOR MYOMECTOMY - Сергей Валерьевич Рыбников; София Камовна Арузуманян; Лариса Николаевна Данилова; Артем Константинович Неретин; Елена Владимировна Рудаева; Игорь Вадимович Пачгин; Вадим Гельевич Мозес; Светлана Ивановна Елгина; Владимир Вячеславович Павленко (The Publishing House Medicine and Enlightenment, 2021)
Myoma of the uterus is one of the most common diseases of the female genital organs. Carrying out myomectomy allows you to preserve the reproductive potential of women. Today, gynecologists are faced with the task of optimizing the examination, selection of patients and the choice of access for a successful low-traumatic myomectomy operation.